Carriage of penicillin-non-susceptible pneumococci among children in northern Tanzania in the 13-valent pneumococcal vaccine era. (April 2019) - Emgård, Matilda; Msuya, Sia E.; Nyombi, Balthazar M.; Mosha, Dominic; Gonzales-Siles, Lucia; Nordén, Rickard; Geravandi, Shadi; Mosha, Victor; Blomqvist, Josefine; Franzén, Sofie; Sahlgren, Fredrika; Andersson, Rune; et al.
Highlights: Pneumococcal carriage among the sampled children was 31% (244/775). Penicillin non-susceptibility increased during 2013–2015 after the introduction of the 13-valent pneumococcal vaccine (PCV13). Non-susceptibility to amoxicillin/ampicillin and ceftriaxone was low. The prevalence of PCV13 serotypes decreased from 56% in 2013 to 23% in 2015. The majority of the children had been treated with antibiotics in the past 3 months. Abstract: Objectives: To determine the antibiotic susceptibility and serotype distribution of colonizing Streptococcus pneumoniae in Tanzanian children. Serial cross-sectional surveys were performed following the national introduction of the 13-valent pneumococcal conjugate vaccine (PCV13) in December 2012. Methods: A total of 775 children less than 2 years of age were recruited at primary health centres in Moshi, Tanzania between 2013 and 2015, and samples were obtained from the nasopharynx. S. pneumoniae were isolated by culture and tested for antibiotic susceptibility by disc diffusion and E-test methods; molecular testing was used to determine serotype/group. Results: Penicillin non-susceptibility in the isolated pneumococci increased significantly from 31% (36/116) in 2013, to 47% (30/64) in 2014 and 53% (32/60) in 2015. Non-susceptibility to amoxicillin/ampicillin and ceftriaxone was low ( n = 8 and n = 9, respectively), while 97% (236/244) of the isolates were non-susceptible to trimethoprim–sulfamethoxazole. The majority of the children (54%, n = 418) had been treated with antibiotics in the past 3 months, and amoxicillin/ampicillin were overall the most commonly used antibiotics. Carriage of penicillin-non-susceptible pneumococci was more common in children with many siblings. The prevalence of PCV13 serotypes among the detected serotypes/groups decreased from 56% (40/71) in 2013 to 23% (13/56) in 2015. Conclusions: Penicillin non-susceptibility in S. pneumoniae colonizing Tanzanian children increased during an observation period shortly after the introduction of PCV13. Measures to ensure rational use of antibiotics and more effective systems for surveillance of antibiotic resistance and serotype distribution are needed to assure continued effective treatment of pneumococcal disease.